`Street science' - An analysis of science-related social beliefs of secondary school students in Trinidad and Tobago - George, June M. (1986)
This study seeks to explain why lower-ability students have been performing poorly on external science examinations. Traditional customs and beliefs that seem to have a scientific base--"street science"--are examined. The study shows that 1) street science abounds in the local community, 2) lower-ability students are highly committed to it, and 3) two-thirds of the information collected is not supported by conventional scientific principles. It is likely that the earlier acquisition of street science by students interfaces with the learning of conventional science in schools
Keywords: Secondary school students